Antimicrobial guidelines in clinical practice: incorporating the ethical perspective - Lambregts, Merel; Rump, Babette; Ropers, Fabienne; Sijbom, Martijn; Petrignani, Mariska; Visser, Leo; de Vries, Martine; de Boer, Mark (JAC-antimicrobial resistance, 2021)
Abstract Introduction Guidelines on antimicrobial therapy are subject to periodic revision to anticipate changes in the epidemiology of antimicrobial resistance and new scientific knowledge. Changing a policy to a broader spectrum has important consequences on both the individual patient level (e.g. effectiveness, toxicity) and population level (e.g. emerging resistance, costs). By combining both clinical data evaluation and an ethical analysis, we aim to propose a comprehensive framework to guide antibiotic policy dilemmas. Methods A preliminary framework for decision-making on antimicrobial policy was constructed based on existing literature and panel discussions. Antibiotic policy themes were translated into specific elements that were fitted into this framework. The adapted framework was evaluated in two moral deliberation groups. The moral deliberation sessions were analysed using ATLAS.ti statistical software to categorize arguments and evaluate completeness of the final framework. Results The final framework outlines the process of data evaluation, ethical deliberation and decision-making. The first phase is a factual data exploration. In the second phase, perspectives are weighed and the policy of moral preference is formulated. Judgments are made on three levels: the individual patient, the patient population and society. In the final phase, feasibility, implementation and re-evaluation are addressed. Conclusions The proposed framework facilitates decision-making on antibiotic policy by structuring existing data, identifying knowledge gaps, explicating ethical considerations and balancing interests of the individual and current and future generations.